Reproductive Health Knowledge of Deaf Students at SLB Negeri Pati - Zakaria Nuril Huda; Herry Widyastono; Sri Yamtinah (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2022)
This research is a quantitative study that aims to determine the level of knowledge of deaf adolescents about reproductive health. This is a preliminary study to be followed by a developmental study. The population and sample of this study were 24 deaf adolescent students at the Pati State SLB who were selected using a saturated sampling technique. The data analysis technique used in this research is descriptive statistics. Data collection was in the form of a test to gather information about the knowledge of deaf students about reproductive health. The results of this study indicate that the majority of the sample is male. Only 6 students or about 17% of the total sample had very good or good knowledge, while 17% had sufficient knowledge and 63% had less knowledge. The number of students with very less knowledge is only 3% of the total sample.